Calculation of Mass Attenuation Coefficients for Pedicle Screw by Theoretical and Monte Carlo Simulation Methods - Hasan Özdoğan; Yiğit Ali Üncü; Onur Karaman; Hakan Çakın (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2021)
Spine fixation is required in cases such as congenital spinal curvatures, vertebral fractures, sagittal collapse over time, painful kyphosis, and bone load due to tumors. Although there are many methods in the literature, the most commonly used spine fixation method is the fixation with pedicle screws. In these cases, it is known that pedicle screws are used frequently in the body. In this study, how the radiological exposure of the pedicle screws in the vertebral column that dose was evaluated by simulation methods. First, the elemental analysis of the pedicle screw was analyzed via Scanning Electron Microscopy (SEM) equipped with the Energy Dispersive X-ray Spectroscopy (EDS). Then, the elemental compositions of the pedicle screw obtained were used for simulation codes. subsequently, the half-value thickness and the attenuation coefficient calculations were conducted for the pedicle screw and vertebral column. Both XCOM software and MCNP (Monte Carlo N-Particle) simulation code were used to obtain photon interaction parameters within the energy range of 60-250 keV.